Management of a Complex Urethrovaginal Fistula Post-pelvic Injury in a Young Female: A Rare Case Report - Vilas P Sabale; Amala Anant Ghalsasi; Vikram P Satav (Journal of Clinical and Diagnostic Research)
Urethral injuries associated with pelvic fractures in female patients are a rare condition. The diagnosis and management of traumatic injury to the female urethra are not well-understood, as the literature on the subject is very limited. Hereby, the authors present a case of a 29-year-old female patient who presented with continuous incontinence. The patient had a history of trauma while riding a bicycle 18 years ago, resulting in a pelvic fracture, bladder rupture, and urethral rupture. She was managed with fracture fixation, bladder repair, and Suprapubic Catheter (SPC) insertion. Urethral repair was performed after six months, but the patient remained incontinent. Upon presentation to our hospital, the patient was diagnosed with vaginal stenosis and a large urethrovaginal fistula. She was managed with vaginoplasty followed by urethrovaginal fistula repair using gracilis muscle interposition. This procedure failed, resulting in the recurrence of the Urethrovaginal Fistula (UVF) and ongoing incontinence. The patient was re-operated, and fistula repair was accomplished using a local vaginal flap. This case highlights the complex nature of urethral injury in females, the challenges posed by delayed complications, and the necessity for multiple procedures.